(untitled) (Journal of Partial Differential Equations, 2018)
This paper concerns the long-time behavior for the 2D incompressible Navier-Stokes-Voight equations with distributed delay on a non-smooth domain. Under some assumptions on the initial datum and the delay datum, the existence of compact global attractors is obtained.